The HMGB1/RAGE axis induces bone pain associated with colonization of 4T1 mouse breast cancer in bone - Tatsuo Okui; Masahiro Hiasa; Shoji Ryumon; Kisho Ono; Yuki Kunisada; Soichiro Ibaragi; Akira Sasaki; G. David Roodman; Fletcher A. White; Toshiyuki Yoneda (Journal of Bone Oncology, 2021)
Bone pain is a common complication of breast cancer (BC) bone metastasis and is a major cause of increased morbidity and mortality. Although the mechanism of BC-associated bone pain (BCABP) remains poorly understood, involvement of BC products in the pathophysiology of BCABP has been proposed. Aggressive cancers secrete damage-associated molecular patterns (DAMPs) that bind to specific DAMP receptors and modulate cancer microenvironment. A prototypic DAMP, high mobility group box 1 (HMGB1), which acts as a ligand for the receptor for advanced glycation end products (RAGE) and toll-like receptors (TLRs), is increased in its expression in BC patients with poor outcomes. Here we show that 4T1 mouse BC cells colonizing bone up-regulate the expression of molecular pain markers, phosphorylated ERK1/2 (pERK) and pCREB, in the dorsal root ganglia (DRGs) innervating bone and induced BCABP as evaluated by hind-paw mechanical hypersensitivity. Importantly, silencing HMGB1 in 4T1 BC cells by shRNA reduced pERK and pCREB and BCABP with decreased HMGB1 levels in bone. Further, administration of a neutralizing antibody to HMGB1 or an antagonist for RAGE, FPS-ZM1, ameliorated pERK, pCREB and BCABP, while a TLR4 antagonist, TAK242, showed no effects. Consistent with these in vivo results, co-cultures of F11 sensory neuron-like cells with 4T1 BC cells in microfluidic culture platforms increased neurite outgrowth of F11 cells, which was blocked by HMGB1 antibody. Our results show that HMGB1 secreted by BC cells induces BCABP via binding to RAGE of sensory neurons and suggest that the HMGB1/RAGE axis may be a potential novel therapeutic target for BCABP.